Sleep Apnea and Inflammation – Getting a Good Night’s Sleep with Omega-3 Supplementation - Scorza, Fulvio A.; Cavalheiro, Esper A.; Scorza, Carla A.; Galduróz, José C.; Tufik, Sergio; Andersen, Monica L. (Frontiers in Neurology, 2013)
Obstructive sleep apnea (OSA) is a multifactorial sleep disorder associated with an increased risk of cardiovascular mortality and morbidity. Several mechanisms have been proposed to explain the association between OSA and cardiovascular dysfunction. One of the proposed mechanisms is an inflammatory response to OSA mediated by tumor necrosis factor (TNF-α). Patients with OSA have higher plasma, serum, and intracellular levels of TNF-α, which may be reduced after apnea treatment with continuous positive airway pressure (CPAP). Because TNF-α plays an important role in OSA related cardiovascular morbidity, the present review aims to identify other preventive measures, in addition to CPAP, that may minimize the inflammatory process in OSA and consequently the risk of premature death due to cardiovascular dysfunction. Thus, we hypothesized that a nutritional immunology profile, i.e., supplementation with omega-3 fatty acids, may be valuable for individuals with OSA.